Novel 1,2,4-triazolethiol-thiophen Hybrids: Facile Synthesis, Characterization, ADMET Prediction and Molecular Docking - Koparir, Pelin; Anwar Omar, Rebaz; Sarac, Kamuran; Koparir, Metin; Safin, Damir A. (Taylor & Francis Ltd, 2024)
In the present contribution, novel 1,2,4-triazolethiol-thiophene hybrids, namely 4-ethyl-5-(thiophen-2-yl)-4H-1,2,4-triazole-3-thiol (1) and 4-phenyl-5-(thiophen-2-yl)-4H-1,2,4-triazole-3-thiol (2), which were readily fabricated from addition of isothiocyanatoethane or isothiocyanatobenzene, respectively, to thiophene-2-carbohydrazide followed by addition a KOH solution to provoke the cyclization to the 1,2,4-triazole ring. The formation of compounds 1 and 2 was firmly confirmed by the means of elemental analysis, IR, 1H and 13C{1H} NMR spectroscopy. The DFT-based computations in gas phase were additionally applied to shed light on the structure and electronic features of the title compounds. Theoretical calculations revealed that for both molecules their corresponding thione derivatives, namely 4-ethyl-5-(thiophen-2-yl)-2,4-dihydro-3H-1,2,4-triazole-3-thione (1') and 4-phenyl-5-(thiophen-2-yl)-2,4-dihydro-3H-1,2,4-triazole-3-thione (2'), are 15.00 and 11.96 kcal/mol, respectively, more energetically favorable in gas phase. However, a comparison of the experimental and calculated IR and NMR spectra testify to the thiol tautomers of compounds 1 and 2 for both compounds in solid state and in DMSO-d6. The chemical activity of 1 and 2 was estimated by reactivity descriptors and MEP surface. ADMET properties of the reported compounds were predicted in silico using online services. Potential inhibition of a series of the tick-borne encephalitis (TBE) proteins by compounds 1 and 2 was studied using molecular docking, which, in turn, allowed to reveal the ligand efficiency scores for the resulting protein-ligand complexes. It was established that compound 1 exhibits the best activity against the tick-borne encephalitis virus Serine protease NS3, while compound 2 is preferable for the RNA-stimulated ATPase activity of tick-borne encephalitis virus helicase.
Keywords: Triazole; thiophene; DFT; molecular docking; tick-borne encephalitis